Financial Well-Being: Psychological Factors that Affect African Americans' Financial Well-Being - Crystal R. Hudson; CW Copeland; John Young (Journal of Financial Therapy, 2022)
Most families strive toward financial security and well-being, which would allow them to weather financial shocks and accomplish their long-term goals. However, African Americans have not experienced the same level of financial well-being as others, and this study explored psychological factors that may affect their financial well-being. Data from the 2016 National Financial Well-Being survey (NFWBS), including the CFPB (Consumer Financial Protection Bureau) Financial Well-Being scale, was utilized in this study. Researchers found that the following factors had a significant positive relationship with the financial well-being of African Americans; grasp of financial skills (confidence), mistreatment with financial services (trust), and health status. Whereas materialism and planning had no significant association with African Americans’ financial well-being.
Keywords: Financial Well-Being; Psychological; African Americans; Personal Finance